AL-MUTARĀDIF DAN AL-MUSYTARAK DALAM AL-QUR’AN : Studi atas Tafsīr Jāmi’ al-Bayān ‘an Ta’wil Āyi Al-Qur’an Karya Aṭ-Ṭabarī - Fuji Faradilla, Ayu (Al-Fath, 2022)
In this paper, we discuss the words al-Mutarādif and al-Musytarak and their application in Tafsir Jāmi’ al-Bayān Fī Ta’wil Al-Qur’an by Aṭ-Ṭabarī. The author is interested in doing this research because he wants to know more about what words are included in the categories of al-Mutarādif and al-Musytarak according to Aṭ-Ṭabarī’s perspective in the application of his book of interpretation. The objectives of this research are as follows: One, to reveal and explain various words and meanings (words of al-Khauf and Khasy-yah, khalaqa, ja’ala, ḍalāl and rahmah) according to the perspective of Al- Mutarādif and Al-Musytarak. Two, To find out Aṭ-Ṭabarī’s interpretation of the alleged words Mutarādif and Musytarak in the Qur'an (the words al-Khauf and Khasy-yah, khalaqa, ja’ala, rahmah, and ḍalāl). Three, To know the views of aṭ-Ṭabarī regarding Mutarādif and Musytarak in the Qur’an. In this thesis the author uses a qualitative approach in the form of library research, by examining library books and scientific works in other forms. The primary source in this research is Tafsir Jāmi’ al-Bayān ‘an Ta’wil Āyi Al-Qur’an by Aṭ-Ṭabarī. The results of this study indicate that, al-Mutarādif is a word that has many words but has one meaning. On the other hand, al-Musytarak is a word that has many or varied meanings. based on what the author examines, the words included in al-Mutarādif are al-Khauf and Khasy-yah, khalaqa, ja’ala. And words that include al-Musytarak are the words rahmah, and ḍalāl.